2022
DOI: 10.1111/jcmm.17481
|View full text |Cite
|
Sign up to set email alerts
|

Novel read‐through fusion transcript Bcl2l2‐Pabpn1 in glioblastoma cells

Abstract: Read‐through fusion transcripts have recently been identified as chimeric RNAs and have since been linked to tumour growth in some cases. Many fusion genes generated by chromosomal rearrangements have been described in glioblastoma. However, read‐through fusion transcripts between neighbouring genes in glioblastoma remain unexplored. We performed paired‐end RNA‐seq of rat C6 glioma cells and normal cells and discovered a read‐through fusion transcript Bcl2l2‐Pabpn1 in which exon 3 of Bcl‐2‐like protein 2 (Bcl2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…21 However, fusion transcripts without corresponding genomic changes have been reported in many cancer types. 11,14,[22][23][24] Choi et al 24 reported that PHOSPHO2-KLHL23 read-through transcript increases KLHL23…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 However, fusion transcripts without corresponding genomic changes have been reported in many cancer types. 11,14,[22][23][24] Choi et al 24 reported that PHOSPHO2-KLHL23 read-through transcript increases KLHL23…”
Section: Discussionmentioning
confidence: 99%
“…In addition, read‐through fusion transcripts are abundantly found in normal tissue 21 . However, fusion transcripts without corresponding genomic changes have been reported in many cancer types 11,14,22–24 . Choi et al 24 reported that PHOSPHO2‐KLHL23 read‐through transcript increases KLHL23 protein expression and increases cell proliferation and resistance to anticancer drug treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various read-through transcripts have been identified with the recent progress in genome analysis, and it has been suggested that these chimeric transcripts can be translated to generate fusion proteins that exhibit new subcellular localization or have special properties [ 17 , 18 ]. In fact, in this study, the fusion of the mitochondrial protein TOMM40 with the secreted protein APOE was found to generate a new mitochondrial protein without the properties of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…CHFR-GOLGA3 and BCL2L2-PABPN1 transcripts are highly expressed in bladder tumours relative to adjacent normal tissue [50]. The BCL2L2-PABPN1 transcript, with oncogenic activity, is also detected in glioblastomas [51]. The functionality of read-through transcripts, whether their mode of action is through the transcript or a protein product, remains to be investigated.…”
Section: Read-through Transcriptsmentioning
confidence: 99%